SALAM DAN UNGKAPAN PERPISAHAN DALAM BAHASA INGGRIS DAN BAHASA MONGONDOW (SUATU ANALISIS KONTRASTIF) - Iroth, Finsensia Indriani; Pelealu, Hetty; Lasut, Theresia M.C (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â Â The title of this skripsi is â€œSalam dan Ungkapan Perpisahan dalam Bahasa Inggris dan Bahasa Mongondow: Suatu Analisis Kontrastifâ€. The aims of this study are to identify, classify, and contrast the forms of greetings and leave takings in English and Mongondow Language in order to find out the similarities and differences between the two languages. In this research, the writer uses descriptive method according to Suryana, sociolinguistic theory of greetings and leave takings by Wardhaugh and contrastive analysis by Lado. Greetings and leave takings in English and Mongondow Language have similarities and differences. For instance, both English and Mongondow Language have two forms, they are formal and informal forms. Greetings and leave takings in English Language have a lot of variations whereas Mongondow Language just has a little bit variations. The difference between English and Mongondow Language is Mongondow Language has special greetings for welcoming guests in a formal situation, but in English Language there is no special greetings for welcoming guests, The research shows that it is important to say greeting and leave taking in our daily conversation and hoped to give additional informations for students of linguistics and other readers who are interested in learning about greeting and leave taking especially in Mongondow Language.——————————————————Keywords : Greetings and leave takings, English and Mongondow Language, Contrastive Analysis